Hubungan Panjang Bobot dan Faktor Kondisi Ikan Terbang Sayap Kuning (Cheilopogon abei Parin, 1996) Di Perairan Majene, Sulawesi Barat - Muhammad Nur; Muhammad Nur Ihsan; Reski Fitriah; Adiara Firdhita Alam Nasyrah; Tenriware (Jurnal Airaha, 2022)
Flying fish yellow wing (Cheilopogon abei Parin, 1996) is one of the flying fish species that have important economic value in West Sulawesi. This study aims to examine the lengthweight relationship and condition factors of flying fish yellow wing to provide basic data for sustainable management efforts. This research was carried out from October 2021 to March 2022. A Sampling of fish was carried out in Mosso Village, Majene Regency, West Sulawesi Province. Sample analysis was carried out at the Integrated Laboratory of the Department of Fisheries, University of West Sulawesi. The total length was measured using a digital caliper with an accuracy of 0.01 mm and the bodyweight of the sample fish was measured using a digital scale with an accuracy of 0.01 g. The results of data collection obtained as many as 104 fish samples, consisting of 59 male fish and 45 female fish. The results of the analysis of the length-weight relationship of the flying fish yellow wing obtained the equation W=0,056L2,556 in the male fish, W=0.0492L2,589 in the female fish, and the combined equation W=0.0003L2.8846. Furthermore, the results of the t-test on fish with a value of b obtained a t count > t table, so that the flying fish’s yellow wing belongs to the negative allometric (minor) growth type where the increase in body length is faster than the increase in body weight. Differences in gonadal maturity, and the availability of different food every month are the main factors causing the negative allometric growth pattern of flying fish in Majene waters. Condition factor male flying fish yellow wing ranged from 0.8712 to 1.2006 with an average of 1.0015 and the female yellow wing flying fish ranged from 0.8528 to 1.1657 with an average of 1.0046. The condition factor of female fish is higher than that of male fish